NAVIGATING ERP CHOICES: A FRAMEWORK FOR EVALUATING ON-PREMISES AND CLOUD-BASED SYSTEMS IN VARIOUS INDUSTRIES - Sharath Chandra Vanam (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article presents a comprehensive comparative analysis of on-premises and cloud-based Enterprise Resource Planning (ERP) systems, addressing the evolving landscape of organizational resource management. Through a systematic review of deployment models, cost structures, scalability, implementation processes, user experiences, and security considerations, we evaluate the strengths and limitations of each approach. Our findings reveal that while on-premises ERP systems offer greater customization and control, cloud-based solutions provide enhanced flexibility, accessibility, and cost-efficiency, particularly for small to medium-sized enterprises. The article highlights the critical factors influencing ERP system selection, including initial and ongoing costs, scalability requirements, data security needs, and industry-specific compliance standards. By examining these factors across various organizational contexts, this article provides a framework for decision-makers to assess and select the most appropriate ERP deployment model. The implications of this article extend to both practitioners navigating ERP implementation decisions and scholars investigating the broader impacts of cloud computing on enterprise systems.